TAPAH MELENGGANG SEBAGAI IDENTITAS BUDAYA KABUPATEN BATANG HARI: KAJIAN SEJARAH, MAKNA SIMBOLIK, DAN NILAI EDUKATIF - Kurnia, Eka Kurnia; Natasya T; Nabilla Najwa Azzahra; Wiwik Kurniyati; Maulidia Alqanita; Deva Merlin Claudia; Ullyl Khoyrul Ummah; Mutiara Ratu Nirmala; Marsya; Zhafira Sayyidatunnisa; Afifa Suci Nahara; Oliver Chelsea Sitanggang; Destrinelli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Tapah Melenggang is a cultural icon of Batang Hari Regency that represents the historical and ecological relationship between the community and the Batanghari River. This symbol not only depicts the tapah fish (Wallago leeri) as a local natural resource but also embodies cultural values shaped through the collective experiences of the Malay community. This study aims to analyze the historical aspects, symbolic meanings, social functions, and educational values of Tapah Melenggang as a form of local cultural identity. This research employs a qualitative approach using a library research method. Data were collected from scholarly journals, academic books, and official documents, and analyzed through descriptive-interpretative techniques based on cultural symbolism theory and local wisdom-based education. Data validity was ensured through source triangulation. The findings indicate that Tapah Melenggang encompasses interconnected historical, symbolic, social, and educational dimensions. The symbol reflects values of strength, resilience, and balance, while also functioning as a collective identity and a contextual learning resource. Its integration into local wisdom-based education contributes to strengthening character development, cultural awareness, and the preservation of local identity in the era of globalization